Methods of Development of Improvement of Special Physical Training of Sambists - Bayturaev Yerlan Isakovich (Zien Journals, 2022)
This article presents scientific research on ways to improve the general and special physical training of sambists in the training process.
Keywords: physical training; technical training; tactical training; methodology